Particle-induced morphological modification of Al alloy equiaxed dendrites revealed by sub-second in situ microtomography. (15th February 2017) - Daudin, R.; Terzi, S.; Lhuissier, P.; Tamayo, J.; Scheel, M.; Babu, N. Hari; Eskin, D.G.; Salvo, L.
Abstract: The study of dendritic growth is a challenging topic at the heart of intense research in material science. Understanding such processes is of prime importance as it helps predicting the final microstructure governing material properties. In the specific case of the design of metal-matrix nanocomposites (MMNCs), the addition of nano-sized particles inside the metallic melt increases the complexity as their influence on the growth morphology of dendrites is not yet fully understood. In the present experimental study, we use in situ X-ray tomography imaging with very high temporal resolution (0.35 s per 3D image) coupled with in situ ultrasonic melt homogenisation to record, in 3D and real time, the free growth at high cooling rates (∼2 K s −1 ) of equiaxed dendrites in an aluminium-based alloy (AA6082) containing Y2 O3 nanoparticles. The careful 3D analysis of the dendrite morphologies as well as their solidification dynamics reveals that in the case of well-dispersed particles, dendrite equiaxed growth occurs through complex hyper-branched morphologies. Such behaviour is believed to arise from particle-induced modification of the solidification processes at the origin of multiple splitting, branching and curving mechanisms of the dendrite arms. These results shed light on long-standing empirical and modelling statements and open new ways for direct investigation of equiaxed growth in metallic alloys and composites. Graphical abstract: Image 1